2020
DOI: 10.1186/s12884-020-03074-9
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study 2005–2015 of all cases of fetal death occurred at ≥23 gestational weeks, in Friuli Venezia Giulia, Italy

Abstract: Background: Intrauterine fetal death (IUFD) is a tragic event and, despite efforts to reduce rates, its incidence remains difficult to reduce. The objective of the present study was to examine the etiological factors that contribute to the main causes and conditions associated with IUFD, over an 11-year period in a region of NorthEast Italy (Friuli Venezia Giulia) for which reliable data in available. Methods: Retrospective analysis of all 278 IUFD cases occurred between 2005 and 2015 in pregnancies with gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…It has been reported that the causes of perinatal mortality change due to the progress in prenatal diagnosis and perinatal management [ 5 - 6 ]. Fresh stillbirth reflects the quality of intrapartum care, while macerated stillbirth reflects antenatal care (ANC) quality [ 7 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the causes of perinatal mortality change due to the progress in prenatal diagnosis and perinatal management [ 5 - 6 ]. Fresh stillbirth reflects the quality of intrapartum care, while macerated stillbirth reflects antenatal care (ANC) quality [ 7 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the fetal death rate of 5.96 per 1,000 live births and fetal deaths, described in the USA (McDorman & Gregory, 2015), was lower than the Latin American stillbirth rate (9.6 per 1,000). Also lower than ReLAMC, the rate of fetal deaths at ≥23 weeks was 2.8 per 1,000 live births, in Friuli Venezia Giulia, 2005 to 2013, excluding TOPFA (Monasta et al, 2020). Lower stillbirth rates were also published for Australia, 7.1 per 1,000, from 2013 to 2014 (Australian Institute of Health and Welfare, 2018), and the U.K. stillbirth rate is 3.74 per 1,000 (Draper et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Intrauterine fetal demise (IUFD) occurs when a fetus dies in utero after 20 weeks of gestation [ 4 ]. The prevalence of IUFD varies greatly between areas and nations, ranging from 2.5 to 8.8 per 1,000 newborns [ 5 ]. The causes of IUFD are multifactorial and include maternal, fetal, and placental factors.…”
Section: Introductionmentioning
confidence: 99%